The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/toxins6031036
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Neurotoxicity of Two Malaysian Krait Species (Bungarus candidus and Bungarus fasciatus) Venoms: Neutralization by Monovalent and Polyvalent Antivenoms from Thailand

Abstract: Bungarus candidus and Bungarus fasciatus are two species of krait found in Southeast Asia. Envenoming by these snakes is often characterized by neurotoxicity and, without treatment, causes considerable morbidity and mortality. In this study, the in vitro neurotoxicity of each species, and the effectiveness of two monovalent antivenoms and a polyvalent antivenom, against the neurotoxic effects of the venoms, were examined in a skeletal muscle preparation. Both venoms caused concentration-dependent inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, when BCAV at 3x recommended titer was added at the t 90 time point, it failed to restore indirect twitches. The inability of antivenom to reverse neurotoxicity is in agreement with previous in-vitro studies [13], and indicates the likely presence of irreversible presynaptic neurotoxins in the venoms [36]. It is also possible that there are unique toxins in BC-M and BC-I which unable to be neutralized by the antivenom.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, when BCAV at 3x recommended titer was added at the t 90 time point, it failed to restore indirect twitches. The inability of antivenom to reverse neurotoxicity is in agreement with previous in-vitro studies [13], and indicates the likely presence of irreversible presynaptic neurotoxins in the venoms [36]. It is also possible that there are unique toxins in BC-M and BC-I which unable to be neutralized by the antivenom.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, B . candidus venoms were found to be more potent compared to the venoms from known neurotoxic elapids previously characterized using the same chick-biventer cervicis nerve-muscle preparation in our laboratory (Table 1) [13,28,29]. However, there were no significant differences in neurotoxicity between B .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Even if the commercial monovalent antivenom in Australia is still polyvalent. 19 Anti snake venom serum of various types of antibodies, more or less residual Fc fragments, which for the human body is a heterologous substance, which caused the occurrence of allergic reactions is reasonable. Some studies showed that it may be feasible to reduce adverse reactions using antivenom prepared with highly immunogenic venom components that produce neutralizing and protective antibody after immunizing animals.…”
Section: Discussionmentioning
confidence: 99%